Layered Wyner–Ziv video coding for transmission over unreliable channels - Xu, Qian; Stanković, Vladimir; Xiong, Zixiang (Signal processing, 2006)
Based on recent works on Wyner–Ziv coding (WZC) (or lossy source coding with decoder side information), this paper considers the case with noisy channel and addresses distributed joint source–channel coding (JSCC), while targeting at the important application of scalable video transmission over wireless networks. In WZC, after quantization, Slepian–Wolf coding (SWC) is used to reduce the rate. SWC is traditionally realized by sending syndromes of a linear channel code. Since syndromes of the channel code can only compress but cannot protect, for transmission over noisy channels, additional error protection is needed. However, instead of using one channel code for SWC and one for error protection, our idea is to use a single channel code to achieve both compression and protection. We replace the traditional syndrome-based SWC scheme by the parity-based one, where only parity bits of the Slepian–Wolf channel code are sent. If the amount of transmitted parity bits increases above the Slepian–Wolf limit, the added redundancy is exploited to cope against the noise in the transmission channel. Using irregular repeat-accumulate codes for practical parity-based SWC, we design a novel layered Wyner–Ziv video coder which is robust to channel failures and thus very suitable for wireless communications. Our simulation results show great advantages of the proposed solution based on JSCC compared to the traditional approach where source and channel coding are performed separately.